The interaction between leadership styles and cultures affecting work outcomes in organizations - Mittra, Neetika (2016)
This review article provides an understanding of the overarching perspectives to how leadership styles interact with different cultures to achieve positive work outcomes and decrease negative work outcomes. It explores five different leadership styles that have been widely documented by scholars, and also multiple cultural dimensions by various theorists. The results show that cultural dimensions such as individualism-collectivism and power distance moderate the work outcomes in organizations, when leadership styles and culture interact.